Acute Effects of Positive Airway Pressure on Functional Mitral Regurgitation in Patients with Systolic Heart Failure - Kato, Takao; Kasai, Takatoshi; Yatsu, Shoichiro; Murata, Azusa; Matsumoto, Hiroki; Suda, Shoko; Hiki, Masaru; Shiroshita, Nanako; Kato, Mitsue; Kawana, Fusae; Miyazaki, Sakiko; Daida, Hiroyuki (Frontiers in Physiology, 2017)
Background: Acute effects of positive airway pressure (PAP) (including continuous PAP [CPAP] and adaptive servo-ventilation, an advanced form of bi-level PAP) on functional mitral regurgitation (fMR) in patients with heart failure (HF) with left ventricular (LV) systolic dysfunction remain unclear. Thus, whether PAP therapy reduces fMR in such patients with HF was investigated. Methods and results: Twenty patients with HF and LV systolic dysfunction defined as LV ejection fraction (LVEF) <50% (14 men; mean LVEF, 35.0±11.5%) with fMR underwent echocardiography during 10-min CPAP (4 and 8 cm H2O) and adaptive servo-ventilation. For fMR assessment, MR jet area fraction, defined as the ratio of MR jet on color Doppler to the left atrial area, was measured. The forward stroke volume (SV) index (fSVI) was calculated from the time-velocity integral, cross-sectional area of the aortic annulus, and body surface area. fMR significantly reduced on CPAP at 8 cm H2O (0.30±0.12) and adaptive servo-ventilation (0.29±0.12), compared with the baseline phase (0.37±0.12) and CPAP at 4 cm H2O (0.34±0.12) (P<0.001). The fSVI did not change in any of the PAP sessions (P=0.888). However, significant differences in fSVI responses to PAP were found between sexes (P for interaction, 0.006), with a significant reduction in fSVI in women (P=0.041) and between patients with baseline fSVI ≥ and < the median value (27.8 ml/m2, P for interaction, 0.018), with a significant fSVI reduction in patients with high baseline fSVI (P=0.028). In addition, significant differences were found in fSVI responses to PAP between patients with LV end-systolic volume (LVESV) index ≥ and < the median value (62.0 ml/m2, P for interaction, 0.034), with a significant fSVI increase in patients with a high LVESV index (P=0.023). Conclusion: In patients with HF, LV systolic dysfunction, and fMR, PAP can alleviate fMR without any overall changes in forward SV. However, MR alleviation due to PAP might be associated with a decrease in forward SV in women with high baseline SV, whereas MR alleviation due to PAP might be accompanied by increased forward SV in patients with a dilated LV.